Do Long-Run Productivity Differentials Explain Long-Run Real Exchange Rates? - Asea, Patrick (IMF Working Papers; Working Paper, 1994)
We develop a two-country, balanced-growth intertemporal general equilibrium model to examine two predictions of the Balassa-Samuelson model, namely that (i) productivity differentials determine the domestic relative price of nontradables and (ii) deviations from purchasing power parity reflect differences in the relative price of nontradables. In our model, the equilibrium relative price of nontradables along the long-run balanced-growth path is determined by the ratio of the marginal products of labor in the tradable and nontradable sectors. The empirical relevance of the Balassa-Samuelson predictions is examined using the Hodrick-Prescott filter to extract long-run components from a panel database for fourteen OECD countries. The evidence indicates that labor productivity differentials do explain long-run, cross-country differences in relative prices. The predicted relative prices, however, are of little help in explaining long-run deviations from purchasing power parity.